2022
DOI: 10.1136/bcr-2022-252676
|View full text |Cite
|
Sign up to set email alerts
|

Large-bowel obstruction secondary to Enterobius vermicularis pseudotumour

Abstract: Enterobius vermicularis infection is typically observed in paediatric patients and manifests with perianal pruritus, but other manifestations or ectopic presentations have been reported in the literature. We present the case of a man in his 60ss with a large-bowel obstruction with symptoms including a 4-day history of progressive abdominal pain, distension, vomiting and absolute constipation. On examination, his abdomen was distended with tinkling bowel sounds on auscultation. Cross-sectional imaging demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This study found the incidence of intestinal obstruction in 1,211 patients with shigellosis to be 2.5% [1]. Various case reports have described intestinal obstruction caused by parasites [5][6][7][8][9][10][11][12], Chlamydia trachomatis [13][14][15], intrauterine device infection [16], mpox [17], and Mycobacterium avium complex infection [18]. To our knowledge, this is the first case report of prolonged ileus caused by shigellosis after bilateral open inguinal hernia repair and open umbilical hernia repair in an adult.…”
Section: Discussionmentioning
confidence: 70%
“…This study found the incidence of intestinal obstruction in 1,211 patients with shigellosis to be 2.5% [1]. Various case reports have described intestinal obstruction caused by parasites [5][6][7][8][9][10][11][12], Chlamydia trachomatis [13][14][15], intrauterine device infection [16], mpox [17], and Mycobacterium avium complex infection [18]. To our knowledge, this is the first case report of prolonged ileus caused by shigellosis after bilateral open inguinal hernia repair and open umbilical hernia repair in an adult.…”
Section: Discussionmentioning
confidence: 70%